2017
DOI: 10.1002/cne.24238
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of afadin in the ultrastructural morphogenesis of mouse hippocampal mossy fiber synapses

Abstract: A hippocampal mossy fiber synapse, which is implicated in learning and memory, has a complex structure in which mossy fiber boutons attach to the dendritic shaft by puncta adherentia junctions (PAJs) and wrap around a multiply-branched spine, forming synaptic junctions. Here, we electron microscopically analyzed the ultrastructure of this synapse in afadin-deficient mice. Transmission electron microscopy analysis revealed that typical PAJs with prominent symmetrical plasma membrane darkening undercoated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 44 publications
(78 reference statements)
3
28
0
Order By: Relevance
“…We have previously shown that the area of PSDs per unit volume of a spine is decreased and that the concentration of PSD‐95 is slightly decreased in the afadin ‐deficient hippocampal mossy fiber synapse (Sai et al . ). Although the exact mechanism for the formation of the incomplete PSDs in the afadin ‐deficient synapse is not known, these structural defects of the PSDs may at least partly explain the impairment of the postsynaptic functions in the afadin ‐deficient cultured hippocampal neurons.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously shown that the area of PSDs per unit volume of a spine is decreased and that the concentration of PSD‐95 is slightly decreased in the afadin ‐deficient hippocampal mossy fiber synapse (Sai et al . ). Although the exact mechanism for the formation of the incomplete PSDs in the afadin ‐deficient synapse is not known, these structural defects of the PSDs may at least partly explain the impairment of the postsynaptic functions in the afadin ‐deficient cultured hippocampal neurons.…”
Section: Discussionmentioning
confidence: 97%
“…Although the detailed role of afadin in this process remains elusive, it may facilitate the docking, priming, endocytosis, and/or recycling processes. The fine structures of the AZs are not sufficiently observed by serial block face‐scanning electron microscopy, but as the immunofluorescence signal for the AZ protein bassoon and the number of the docked SVs are decreased (Sai et al …”
Section: Discussionmentioning
confidence: 99%
“…Nectins bind with the adaptor protein, afadin, to form the nectin–afadin complex, which further cooperates with the N‐cadherin‐catenin complex in the puncta adherentia junctions (PAJs) (Mizoguchi et al, ; Tachibana et al, ; Togashi et al, ). Using the afadin ‐deficient mouse model, studies have shown that afadin deletion disrupts PAJs, reduces spine density, and alters the ultrastructural morphogenesis in the hippocampus (Beaudoin et al, ; Majima et al, ; Sai et al, ). Afadin deletion also induces nectin mislocation in the DG (Majima et al, ), without affecting nectin expression levels, suggesting that afadin may serve as a downstream molecule of nectins (Beaudoin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We have further shown by serial block face‐scanning electron microscopy that the complexity of the postsynaptic spines and the mossy fiber boutons, the number of the spine heads, the area of the PSDs, and the density of the SVs docked to the AZs are decreased in the afadin ‐deficient synapse (Sai et al . ). Subsequently, using the same afadin ‐deficient mouse line, we have investigated the roles of afadin in the functional differentiation of the hippocampal mossy fiber synapse and shown electrophysiologically that both the release probability of glutamate and the postsynaptic responsiveness to glutamate are markedly reduced in the afadin ‐deficient mossy fiber synapse, whereas neither long‐term potentiation nor long‐term depression is affected (Geng et al .…”
Section: Introductionmentioning
confidence: 97%
“…Afadin plays a role in the formation of the PAJs by first binding to both presynaptic nectin‐1 and postsynaptic nectin‐3 and then binding to αN‐catenin, eventually recruiting N‐cadherin via its direct binding protein ÎČ‐catenin to the adhesion sites formed by the trans ‐interaction of nectin‐1 and nectin‐3 (Sai et al . ). In contrast, the modes of action of afadin in other differentiation processes of the mossy fiber synapse have not been investigated.…”
Section: Introductionmentioning
confidence: 97%